Analysis Flow Velocity and Flow Type Characterization of Noelmina River (Case Study: KM 62.3 Timor Raya Road) - Sri Santi L. M. F Seran; Azarya Bees; Gregorius Paus Usboko; Wenceslaus Reinaldo Fernandez; Goldelfridus Alfredo Abani (Politeknik Siber Cerdika Internasional, 2026)
Background: River flow characteristics play a crucial role in controlling erosion processes, especially in river segments adjacent to infrastructure. The Noelmina River at Km 62.3 Timor Raya Road experiences repeated bank erosion that threatens road stability and nearby public facilities. Objective: This study aims to analyze flow velocity, determine flow characteristics using the Froude and Reynolds numbers, and recommend appropriate riverbank protection structures to reduce erosion risk. Methods: A quantitative field survey was conducted at three observation points (upstream, bend, and downstream). Flow velocity was measured using a current meter at different depth intervals. Hydraulic characteristics were analyzed using average velocity calculations, the Froude number for flow regime classification, and the Reynolds number for flow-type determination. Results: The average flow velocities were 2.298 m/s (Point 1), 1.686 m/s (Point 2), and 1.062 m/s (Point 3), showing a decreasing trend along the river segment. All Froude numbers were below 1, indicating subcritical flow conditions. Reynolds number analysis showed transitional flow at Points 1 and 2, and laminar flow at Point 3. Higher velocities at the river bend indicate greater erosion potential. Conclusion: The river exhibits subcritical flow with varying transitional and laminar characteristics. Recommended mitigation measures include gabions, interlocking concrete blocks, retaining walls, and weirs to reduce flow energy and prevent further bank erosion.